The Effect of Using Project-Based Learning Method on Students’ Speaking Skill in ELT Classes at Vocational School - Meidiyani, Resky; Farahdiba, Syarifah; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This research was a pre-experimental study with one group pre-test and a post-test design, which aims to investigate whether or not the Project-Based Learning method has a significant effect on improving students' speaking skills of class X DKV SMK 3 Parepare students. The sample in this study was 25 students using the cluster random sampling technique. This research used a speaking test as a data collection instrument. The results of this test were used to the effect of significant from implementing the PBL method on students’ speaking skill of class X DKV SMK 3 Parepare students after treatment. It can be proven that the t-test value is smaller than P (0.000 < 0.05), which means that (H0) of this research is rejected and (H1) is accepted. Therefore, it can be concluded that the PBL method has a significant effect on improving students’ speaking skill.